107k views
4 votes
Multiply: (3x + 7)(5x2 − 3x + 6) A) 15x3 + 26x2 − 39x + 42 B) 15x3 + 26x2 + 3x + 42 C) 15x3 − 44x2 − 3x + 42 D) 15x3 + 26x2 − 3x + 42

User Jdamp
by
5.3k points

1 Answer

3 votes

Answer:


\Huge\boxed{15x^3+26x^2-3x+42}

Explanation:


\text{Use FOIL:}\\\\(a+b)(c+d)=ac+ad+bc+bd


(3x + 7)(5x^2-3x + 6)\\\\=(3x)(5x^2)+(3x)(-3x)+(3x)(6)+(7)(5x^2)+(7)(-3x)+(7)(6)\\\\=15x^3-9x^2+18x+35x^2-21x+42\\\\\text{combine like terms}\\\\=15x^3+(-9x^2+35x^2)+(18x-21x)+42\\\\=15x^3+26x^2-3x+42

User Longblog
by
6.3k points